Efeito agudo do exercício aeróbico intervalado de alta intensidade comparado ao aeróbio contínuo moderado sobre o status cardiometabólico e função endotelial em pacientes diabéticos tipo 2 - Arruda, Regiane Maria da Costa (2021)
Introduction: A sedentary lifestyle has been recognized as an independent risk factor for the premature development of coronary heart disease (CHD) and physical inactivity is associated with at least a two-fold increase in the risk of coronary events. It is known that regular exercise is associated with a significant reduction in cardiovascular risk and helps prevent primary and secondary cardiac events. However, the mechanism by which physical exercise promotes the reduction of cardiovascular events has not been fully elucidated. Objectives: Study 1: To analyze the effects of a single session of high-intensity interval aerobic exercise (HIIT) and moderate continuous exercise (MOD) on cardiometabolic status and endothelial function in type 2 diabetic individuals. Study 2: Verify the relationship between FMD and recovery of heart rate and physical capacity in type 2 diabetic patients. Methodology: Study type: controlled clinical trial. Thirty sedentary individuals with DM2 were evaluated. The sample consisted of 19 women and 11 men (mean age 55.30 ± 12.58 years). Brachial artery flow-mediated dilatation (FMD%) was evaluated before and after 30 minutes of exercise. The physical exercise protocol was performed on a treadmill and totaled 24 minutes; was composed of 5 minutes of warm-up, 14 minutes of HIIT (10x30 seconds with intensity 85 to 100% of the maximum heart rate with 1 minute of active pause between sprints), and 5 minutes of cool down, the MOD exercise was performed in the same treadmill with same volume totaling 24 minutes (50 to 70% of heart rate) Results: Study 1: A significant acute effect of exercise on endothelial function (FMD%) and anterograde and retrograde shear stress (respectively, MOD - 0.24 ± 0.39 and HIIT 0.16 ± 0.45; MOD 116.7 (64-170.7) and HIIT 201.4 (155-246.6); MOD -13 (-17.1[- 4.1])) and HIIT -6.9 (-10.8 [-0.6]); p ≤ 0.05). Study 2: We observed that patients do not have low heart rate recovery, with Δ HR 18 ± 5, but 100% of the evaluated patients had reduced physical capacity, ISWT 60.80 ± 19.51 % predicted and there was a correlation in the tools of prognostic evaluation. Conclusion: Study 1: HIIT proved to be more effective for possible cardiovascular protection, even though both exercises had a positive response to glycemic control in type 2 diabetic patients. The exercises presented can be easily performed in clinical practice. Study 2: We conclude that the higher the %FMD, the greater the physical capacity of patients with DM2 and the recovery of heart rate, which may support a good prognosis. Assessments can be easily performed in clinical practice. To analyze the effects of a single session of high-intensity interval aerobic exercise (HIIT) and moderate continuous exercise (MOD) on cardiometabolic status and endothelial function in type 2 diabetic subjects.